CBSX2 is required for the efficient oxidation of chloroplast redox‐regulated enzymes in darkness - Yonghong Li; Lin Zhang; Yurou Shen; Lianwei Peng; Fudan Gao (Plant Direct, 2023)
Abstract Thiol/disulfide‐based redox regulation in plant chloroplasts is essential for controlling the activity of target proteins in response to light signals. One of the examples of such a role in chloroplasts is the activity of the chloroplast ATP synthase (CFoCF1), which is regulated by the redox state of the CF1γ subunit and involves two cysteines in its central domain. To investigate the mechanism underlying the oxidation of CF1γ and other chloroplast redox‐regulated enzymes in the dark, we characterized the Arabidopsis cbsx2 mutant, which was isolated based on its altered NPQ (non‐photochemical quenching) induction upon illumination. Whereas in dark‐adapted WT plants CF1γ was completely oxidized, a small amount of CF1γ remained in the reduced state in cbsx2 under the same conditions. In this mutant, reduction of CF1γ was not affected in the light, but its oxidation was less efficient during a transition from light to darkness. The redox states of the Calvin cycle enzymes FBPase and SBPase in cbsx2 were similar to those of CF1γ during light/dark transitions. Affinity purification and subsequent analysis by mass spectrometry showed that the components of the ferredoxin‐thioredoxin reductase/thioredoxin (FTR‐Trx) and NADPH‐dependent thioredoxin reductase (NTRC) systems as well as several 2‐Cys peroxiredoxins (Prxs) can be co‐purified with CBSX2. In addition to the thioredoxins, yeast two‐hybrid analysis showed that CBSX2 also interacts with NTRC. Taken together, our results suggest that CBSX2 participates in the oxidation of the chloroplast redox‐regulated enzymes in darkness, probably through regulation of the activity of chloroplast redox systems in vivo.